Optimized Protocol for the Detection of Multifunctional Epitope-Specific CD4+ T Cells Combining MHC-II Tetramer and Intracellular Cytokine Staining Technologies - Pastore, Gabiria; Carraro, Monica; Pettini, Elena; Nolfi, Emanuele; Medaglini, Donata; Ciabattini, Annalisa (Frontiers in Immunology, 2019)
Analysis of multifunctional CD4+ T cells is fundamental for characterizing the immune responses to vaccination or infections. Peptide-MHC tetrameric complexes represent a powerful technology to detect antigen-specific T cells by the specific binding to their T cell receptor, and their combination with functional assays is fundamental for characterizing the antigen-specific immune response. Here we optimized a protocol for the detection of multiple intracellular cytokines within epitope-specific CD4+ T cells identified by the MCH class II tetramer technology. The optimal procedure for assessing the functional activity of tetramer-binding CD4+ T cells is based on the simultaneous intracellular staining with both MHC tetramers and cytokine-specific antibodies upon in vitro restimulation of cells with the vaccine antigen. The protocol was selected among procedures that differently combined the steps of cellular restimulation and tetramer staining with intracellular cytokine labelling. This method can be applied to better understand the complex functional profile of CD4+ T cell responses upon vaccination or infection.